Tamil Brahmi Inscription Belonging to 2200 years ago, Discovered by German Archaeological Team in Southern Sri Lanka. - Pushparatnam, P. (University of Jaffna, 2014)
As a general rule, interpretations, Brahmi potsherds, copper plates, seals and coins, among others, provide reliable information to trace the beginning, development and evolution of a language of a region or country. The Brahmi inscriptions play an important part in tracing the history of Sri Lankan languages. These Brahmi inscriptions which belong to the 3rd century B.C. to the 4th century A.D., tell about the message relevant to Buddhism. Scholars like Professor Paranavithana who studied the above inscriptions comment that they are evidences to show that the ancestors of the Sinhala race and their culture came from the North India and the Prakrit language is the forerunner of the old Sinhala language. Scholars like Professor Karunaratna who studied the above inscriptions, considering the unique Tamil letters, names and words, are of the opinion that the Brahmi letters and writing which were introduced from South India were in use in Sri Lanka, before the introduction of Brahmi letters to Sri Lanka with the advent of Buddhism from North India [1]. Recent Archaeological studies in South Sri Lanka and Northern Sri Lanka and the evidences of Brahmi inscriptions and Brahmi potsherds, coins, seals and copper plates provide adequate evidences to show that the use of Tamil language was prevalent in Sri Lanka, since the 3rd century B.C. These evidences show the antiquity of the Tamil language. Among these evidences, the discovery of the Brahmi inscribed pottery at Tisamarahama in the Hambantota District in Southern Sri Lanka by the German Archaeological team need special mention. This inscription which belongs to the 2nd century B.C. was written in the Tamil language with Tamil scripts. However, there are differences of opinion among scholars about the reading and interpretation of the above inscription. The objective of this research is too re-read and scrutinizes the above inscription to derive a profound interpretation of it.